Assessment of Knowledge and Attitude of Colostrum among Postnatal Mothers - Kareema Ahmad Hussein; Afifa Radha Aziz (College of Nursing,University of Mosul, 2013)
Background and aim: colostrum is the first milk produced by the mammary glands of mammals in late pregnancy just prior to giving birth and continuing through the early days of breastfeeding. The study aimed to assess knowledge and attitude of colostrum among postnatal mothers and to find out the association between knowledge and attitude of mothers with demographic characteristics. Materials and method: cross sectional study, deals with 300 mothers who attending to Babylon maternal and child hospital and Alkather health centre. A questionnaire was used to collect the data from the period of 21 November 2012 to 15 March 2013. Data were analyzed by using descriptive and inferential statistical (percentage, frequency, and chi -square). Results : the study shows that the majority of mothers age between (30-39) years was 59% ,also there are significant relationship between the attitude of mothers with some of demographic characteristics of mothers . Conclusion: The study concludes that there is significant relationship between mothers knowledge with their demographic characters at P ≥ 0.5 and there is significant relationship between mothers' attitude with their demographic characterize. Keywords: Knowledge, Attitude, Colostrum, Postnatal Mothers.